RITUALS, TRAINING AND COMMUNITY BUILDING: UNDERSTANDING THE FUNCTIONS OF THE RENGMA NAGA MORUNG - Tep, Gwasole (International Journal of Research -GRANTHAALAYAH, 2024)
In the olden days, the most important institution was the morung or bachelor’s dormitories. It is also called as “Rensika” by the Rengma Nagas. The morung served as a traditional institution which imparted various skills of art and warfare, transmitted the customs and laws from generation to generation and morung evolved to meet the needs and requirements of society. There are different names like men’s club, men’s hall, public school, youth house etc. Like most of the other Naga communities. The Rengma Naga morung acted as a key institution. Every village is divided into khel and each khel has its own morung, which occupies the central place. It has separate morung for both boys and girls. The objective of the study is to understand more deeply the significant role of morung in thesocial, economic and spiritual life of the people. It also aims to create awareness among the present generation on the roles and responsibilities of the youth in promoting value-based society as taught in the morung. The nature of “Rensika” is to be understood more objectively to get a better understanding of society as a whole.Through ethnographic research and community engagement, this paper aims to preserve age old traditions fostering unity among the Rengma Naga people contributing to the resilience of the cultural heritage.